Luteal insufficiency in a bitch: a case description - Sánchez R., Alfonso (2015)
The present report describes and discuss the case of a French bulldog bitch, 2 years and 3 months old with a gestation of about 37 days and vaginal bleeding for nearly 12 days. Infection by B. canis was discarded by serological examination. Determination of serum progesterone through commercial kit showed a low value (2.5-5 ng/ml) so supportive therapy was instituted by micronized progesterone (100 mg/day) until the cessation of vaginal bleeding and maintenance of pregnancy. Progesterone value at this point showed higher values (>5 ng/ml). After day 42 of gestation, hormone supplementation was modified to 100 mg every 48 hours and stopped on day 58 of pregnancy. The female gave birth to a live puppy and other three were removed by cesarean section (two alive and one dead).